2022
DOI: 10.1111/ijac.14085
|View full text |Cite
|
Sign up to set email alerts
|

The fabrication of porous mullite ceramics based on the different sizes of aluminum hydroxide

Abstract: In this research, for studying the influence of size and heat treatment temperature of initial Al(OH) 3 on the physical properties of porous mullite ceramics, porous mullite ceramics were prepared by in situ reaction sintering of amorphous silica and treated Al(OH) 3 . The transition phases χ-Al 2 O 3 , к-Al 2 O 3 , and stable phase α-Al 2 O 3 can be obtained in turn when the treatment temperature of raw Al(OH) 3 is 500, 1000, and 1500 • C, respectively. The coarser the raw Al(OH) 3 , the higher the strength o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…[36], primarily consists of quartz and muscovite. It has been reported that gibbsite (Al(OH) 3 ) undergoes thermal dehydration and phase transformation between 500 and 900°C to form ρ‐Al 2 O 3 37,38 . Other researchers have found that gibbsite could produce porous Al 2 O 3 during heating 38 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[36], primarily consists of quartz and muscovite. It has been reported that gibbsite (Al(OH) 3 ) undergoes thermal dehydration and phase transformation between 500 and 900°C to form ρ‐Al 2 O 3 37,38 . Other researchers have found that gibbsite could produce porous Al 2 O 3 during heating 38 .…”
Section: Resultsmentioning
confidence: 99%
“…Mullite (3Al 2 O 3 ·2SiO 2 ) was identified as a significant crystalline phase and cristobalite as a minor crystalline phase. The intensity of the cristobalite is expected to reduce with the rise in sintering temperature 38 . Lithomargic clay‐WTS mixtures had sharper and well‐defined mullite peaks than WTS‐kaolin clay bricks.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations